Design and fabrication of microfluidic system for high flow rate applications - Wee, Yong Jun. (2010)
High flow rate microfluidic system is an important field of study as it offers novel Lab-on-a-chip capabilities to macro-system applications. One major motivation is microbial detection in water systems to allow more efficient and faster water quality monitoring. This project addresses the issues facing high flow rate microfluidic systems, which are high pressure on chip and unstable interfacing between macro- and micro- components. From analytical design, a Split-And-Recombine-Split-Curve microfluidic chip design was introduced with localized microbial detection points based on numerical modeling and Computation Fluid Dynamics simulations. From fabrication design, high-aspect-ratio (up to 10) microchannels were achieved using the Constant-Volume-Injection as well as high bond strength (more than 60psi) in PDMS microchip using adhesive bonding. These design issues targeted a reduction in flow impedance and higher tolerance level on chip. Experimental results showed that a high flow rate of 240ml/min can be attained in a microfluidic system with maximum pressure of 60psi. This system was then packaged to achieve leak-free, pulse-less and continuous fluidic flow, ready for application in water-borne microbial detection systems.